Preparation of Polyamidoamine Dendrimer Modified Magnetic Nanoparticles and Its Application for Reliable Measurement of Sudan Red Contaminants in Natural Waters at Parts-Per-Billion Levels - Yalin Wu; Yalin Wu; Huahua Bai; Qingxiang Zhou; Shuangying Li; Yayang Tong; Jinghan Guo; Boyao Zhou; Zhi Li; Yali Zhan; Menghua Liu; Yanhui Li; et al. (Frontiers in Chemistry, 2021)
The health threat from Sudan red dyes has been the subject of much attention in recent years and is crucial to design and establish reliable measurement technologies. In the present study, a new magnetic nanomaterial, polyamidoamine dendrimer-modified magnetic nanoparticles (Gn-MNPs), was synthesized and characterized. The nanomaterials had good adsorption capacity for Sudan dyes from natural waters. G1.5-MNPs possessed excellent adsorption capacity and a linear adsorption relationship over the range from 0.02 to 300 μg L−1 of Sudan dyes with relative coefficients all larger than 0.996. The sensitivity of the proposed method was excellent with detection limits over the range from 1.8 to 5.5 ng L−1 and the precision was less than 3.0%. G1.5-MNPs showed a remarkable application potential for the enrichment of trace environment pollutants in aqueous samples and the developed method based on this nanomaterial could be a robust and reliable alternative tool for routine monitoring of such pollutants.